Mobilizing in Uncertainty : Collective Identities and War in Abkhazia - Shesterinina, Anastasia, 1986- (Book collections on Project MUSE., 2021)
"This book looks at participants and nonparticipants in the Georgian-Abkhaz war of 1992-1993 to reveal how ordinary people navigate the uncertainty at the onset of war to arrive at different mobilization decisions, from fleeing to fighting"--